Transdermal delivery of antenatal steroids to promote fetal lung maturation: Proof of principle data from sheep and non-human primate models - Sean W. D. Carter; Ayça Altay Benetti; Ryan Tze Liang Sia; Giorgia Pastorin; Erin L. Johnson; Kay Yi Michelle Seah; Haruo Usuda; Hannah R. S. Watson; Yusaku Kumagai; Qin Wei; Xiawen Liu; Roberto Orefice; et al. (BMC Medicine)
Abstract Background Antenatal steroids (ANS) are routinely administered to women at risk of preterm birth to accelerate fetal lung maturation. Despite extensive clinical use, dosing and route of ANS administration remain unoptimized beyond intramuscular (IM) injection. We aimed to undertake a proof-of-principle assessment of transdermal ANS administration for accelerated fetal lung maturation. Methods We formulated and tested a transdermal ANS (betamethasone) patch in ex vivo studies. To confirm in vivo transdermal distribution of the ANS patch, we undertook a 24-h pharmacokinetic study in non-pregnant cynomolgus macaques (NHP). To assess the efficacy of transdermal betamethasone on fetal lung maturation, we used a preterm sheep model of pregnancy comparing postnatal ventilation outcomes. Date mated ewes received either of the following: (i) IM normal saline (Saline Control, n = 13); (ii) IM ANS (betamethasone) delivery 2 or 8 days post-treatment (2-Day IM ANS, n = 14; 8-day IM ANS Group, n = 6); (iii) IM saline + 2 × transdermal ANS (Betamethasone) patches delivery 2 days post-treatment (2-Day ANS Patch, n = 10); or (iv) IM saline + 2 × transdermal ANS (betamethasone) patches replaced with 2 × new patches after 48 h, delivery 8 days post-treatment (8-Day ANS Patch, n = 11). Lambs were delivered at 123 ± 1 dGA (term 150 days), then ventilated for 30 min to assess lung maturation status. Arterial blood gas, delivery, and ventilation data were analyzed (p < 0.05 significant). Results Transdermal administration of ANS in NHPs achieved rapid plasma accumulation, with a plasma half-life of 8.9 h, similar to that achieved with IM dosing in clinical practice. In preterm sheep, all 2- and 8-day IM and transdermal ANS patch groups had clinically important and statistically significant improvements in ventilation parameters (umbilical PaCO2, pH, tidal volume) compared to saline control. Conclusions We demonstrate, for the first time, the potential for using transdermal ANS for preterm fetal lung maturation. Transdermal ANS administration eliminates the need for injections, pain, and infection risk. Moreover, transdermal ANS delivery demonstrates advantages in dose control, continuity of exposure, and potential to remove drug exposure should the risk of preterm birth resolve. Further development of this technology may improve preterm outcomes through delivery of a low dose, constant fetal steroid exposure.